Pengaruh Edukasi Berbasis Telenursing Terhadap Kemampuan Buruh Angkut dalam Melakukan Pertolongan Pertama Pada Kecelakaan Kerja di TPA Sumompo Kota Manado - Norman A. Talibo; Riskan H. Djafar; I Made Rantiasa (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
. A work accident is an unpredictable event. When it happens, it is important to provide first aid in work accidents and to do it one must have knowledge. To increase knowledge about this first aid, it can be done by providing telenursing-based education. The purpose of this research was to find out the effect of telenursing-based education on the cognitive ability of garbage collector in performing first aid in a work accident. This research was conducted by using a quasi-experimental one group pre-test and posttest design. The population as many as 40 people and sample amounted to 15 respondents which was taken using non-probality sampling technique. This research used Whatsapp application and data collection was done by giving questionnaires in the form of link to pre test and posttest. Then, the collected data was analyzed by a Wilcoxon statistic test. From the wilcoxon test, it was obtained that ρ value = 0,002 in which this ρ value < α = 0,05 meaning Ha was accepted and Ho was rejected. The conclusion of this research is that there is an effect of telenursing-based education on the cognitive ability of garbage collector in performing first aid in a work accident.